2017
DOI: 10.1590/1516-3180.2016.027728102016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal anxiety on child anxiety during dental care: cross-sectional study

Abstract: CONTEXT AND OBJECTIVES: Anxiety is usually classified as a disorder of neurotic nature and is often related to contexts of stress, which may include worries, motor tension and autonomic hyperactivity. The aim of this study was to assess the influence of mothers' anxiety on their children's anxiety during dental care. DESIGN AND SETTING: Analytical cross-sectional study conducted at in a private dentistry school in the south of Brazil. METHODS: Convenience sampling was used. All mothers of children undergoing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 12 publications
6
31
0
14
Order By: Relevance
“…Interestingly, certain other reports concluded that dental anxiety increases with age . This could be explained by the possibility of other factors arising, such as children having had more previous painful dental experiences …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Interestingly, certain other reports concluded that dental anxiety increases with age . This could be explained by the possibility of other factors arising, such as children having had more previous painful dental experiences …”
Section: Discussionmentioning
confidence: 96%
“…Several factors have been reported as contributing factors which influence and affect the level of DFA in children . The age of the child is considered to be one of the factors which has a substantial impact on dental anxiety among children . There is an almost total agreement in the literature that younger children tend to be more anxious in the dental office compared to older children .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective coping with dental fear is extremely important in both adult and paediatric patients. As researchers suggest, the fact that a woman suffers from dental anxiety might be an important factor in the development of the condition in question in her child [4]. In order to overcome the phobia, a dental professional should choose a method corresponding to the anxiety level [5].…”
Section: Introductionmentioning
confidence: 99%